JavaScript prototypes 2025 a complete course to benefit you the most (Packt Publishing, 2024)
Unlock the secrets of JavaScript's prototypal inheritance system and transform how you approach object-oriented programming. This course takes you from foundational concepts like [[Prototype]] objects and the Object.create() method to advanced instantiation patterns and real-world implementation techniques. Each topic is meticulously structured to build your understanding and confidence in applying JavaScript prototypes to your own projects. As you progress, you'll uncover practical insights into constructing prototype chains, differentiating between __proto__ and .prototype, and leveraging inheritance for optimal code reusability. Learn to build, extend, and manipulate prototype-based and class-based models while avoiding common pitfalls. With hands-on examples and a step-by-step guide to complex inheritance patterns, you'll master how JavaScript's object model empowers modern software development. This course concludes with advanced comparisons of prototypal and classical object-oriented programming paradigms, introducing best practices for when to use each. Whether you're building scalable systems or experimenting with composition patterns, this course equips you with the skills to thrive in the JavaScript ecosystem.